SOCIAL MEDIA TRENDS IN SOCIETY CONTEMPORARY SPECTACLE - Dewa Nyoman Wija Astawa (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2025)
The social media phenomenon of the past two decades has marked a profound transformation in the communication structures and consciousness of contemporary society. Drawing on the theories of the society of the spectacle (Debord, 1967) and simulacra (Baudrillard, 1994), this article examines how social reality is now shaped, engineered, and commodified through spectacular digital representations. Using a critical literature review of academic literature and industry reports from 2014–2025, seven key trends characterize today’s society of the spectacle: (1) the dominance of the attention economy; (2) the algorithmization of experience and content; (3) the rise of the creator economy and micro-celebrities; (4) the politicization of the spectacle through the role of influencers; (5) the commodification of authenticity as an affective strategy; (6) the expansion of live commerce and social shopping, particularly in Indonesia; and (7) the growth of synthetic content and deepfakes, which have triggered a crisis of public trust. The findings suggest that cultural authority is shifting from media institutions to digital platforms and individual creators, while algorithms are becoming new determinants of the distribution of social meaning. Ethical implications include the urgent need for algorithmic transparency, accountable content moderation, and strengthening evidence-based media literacy. This study emphasizes that contemporary spectacle society is not simply a visual phenomenon, but rather an economic and epistemological structure that governs how we perceive, interact with, and trust digital reality.